Dyeing cotton fabrics with natural mordant dyes plant origin - Sutlović Ana; Peček Vedrana; Brlek Iva (Tekstilna industrija)
Given the global problems of the textile industry, there is increasing interest in revitalizing the use of natural dyes, with an emphasis on cellulose materials. This investigation presents the dyeing of cotton with natural mordant dyes plant origin. The following dye sources were selected: Stems and leaves of goldenrod, willow bark, stems with leaves and flowers of St. John's wort, hawthorn twigs with leaves and oak galls. All selected plants belong to the group of acid-mordant dyes due to their dyeing properties and bind to the fabric by forming a complex with metal salts (mordants). For this reason, the cotton material was treated with potassium aluminium sulphate dodecahydrate KAl(SO4)2 ·12H2O and iron(II) sulphate heptahydrate FeSO4·7H2O. Through the formation of the ligand: cotton fibre - metal ion - natural mordant dye, a wide range of harmonious shades was obtained. The dyes obtained were evaluated by subjective and objective spectrophotometric analysis. In addition, the fastness to laundering and artificial light was tested, which guarantees both the aesthetic and functional quality of the cotton fabrics dyed in this way.